2020
DOI: 10.1108/pijpsm-08-2020-0139
|View full text |Cite
|
Sign up to set email alerts
|

“Black, white and gray”–A qualitative study of how Swedish police officers describe occupational knowledge

Abstract: PurposeThe purpose of this study is to explore how Swedish police officers describe occupational knowledge. By learning more about how officers describe occupational knowledge, the study gives more insight about the types of information that they may be more likely to adopt in their occupational tasks.Design/methodology/approachIn this study, the author conducted 27 semi-structured interviews with Swedish police officers. I asked officers several open-ended questions about their everyday work life and professi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…While experience and knowledge are terms commonly used, the meaning of these terms is dynamic and can vary depending on the context in which they are discussed (Hoel and Barland, 2020). Although this paper does not aim to discuss how officers understand and perceive knowledge (i.e., Eliasson, 2020), it is essential to understand how concepts such as knowledge and experience are conceptualized.…”
Section: Knowledge and Experiencementioning
confidence: 99%
See 4 more Smart Citations
“…While experience and knowledge are terms commonly used, the meaning of these terms is dynamic and can vary depending on the context in which they are discussed (Hoel and Barland, 2020). Although this paper does not aim to discuss how officers understand and perceive knowledge (i.e., Eliasson, 2020), it is essential to understand how concepts such as knowledge and experience are conceptualized.…”
Section: Knowledge and Experiencementioning
confidence: 99%
“…On the other hand, knowledge is often thought of as information obtained through academic or theoretical contexts. (Aas, 2016;Karp and Stenmark, 2011;Eliasson, 2020). Several studies have found that the differences between these two concepts are highlighted when officers discuss what type of expertise they think are the most important in their occupational role Gottschalk and Dean, 2010;Fekjaer et al, 2014;Back, 2015).…”
Section: Knowledge and Experiencementioning
confidence: 99%
See 3 more Smart Citations